Neutrophil-Related Ratios Predict the 90-Day Outcome in Acute Ischemic Stroke Patients After Intravenous Thrombolysis - Gao, Beibei; Pan, Wenjing; Hu, Xueting; Huang, Honghao; Ren, Junli; Yang, Chenguang; Zhou, Xinbo; Zeng, Tian; Hu, Jingyu; Li, Shengqi; Gao, Yufan; Zhang, Shunkai; et al. (Frontiers in Physiology, 2021)
BACKGROUND AND PURPOSE: Mounting researches have illuminated that neutrophils-related ratios were related to the prognosis of acute ischemic stroke (AIS). However, few have compared their predictive value and accuracy. To make such comparison and identify the best indicator on 90-day outcome, we investigated biomarkers including neutrophil ratio (Nr), neutrophil count (Nc), lymphocyte (L), neutrophil-to-lymphocyte ratio (NLR), platelet (P or PLT), platelet-to-neutrophil ratio (PNR), NLR-to-platelet ratio (NLR/PLT), eosinophil (E), neutrophil-to-eosinophil ratio (NER), monocyte (M) and monocyte-to-neutrophil ratio (MNR). METHODS: This retrospective study recruited 283 AIS and 872 healthy controls (HCs) receiving intravenous thrombolysis (IVT). Blood samples were collected on 24 hours admission before IVT. Propensity Score Matching (PSM) were used to explore whether these ratios differentiated AIS and HCs. We applied univariate and multivariate analyses to evaluate the prediction effect of these ratios separately or added in the model and figured out a clinical predict model. To estimate the discrimination and calibration of new models, the receiver operating characteristics (ROC) curve analysis, DeLong method and likelihood ratio test (LR test) were utilized. RESULTS: PSM showed that Nr, Nc, NLR, P, PNR, NLR/PLT, NER and MNR facilitates the differentiation of the HCs and AIS. Among the eight, PNR and MNR could differentiate 90-day outcome, and PNR performed better. Univariate regression analysis demonstrated that PNR was the only independent predictor which needs no adjustment. Besides, Multivariate regression analysis, Delong method and LR test indicated that among neutrophils-related ratios, NLR, PNR, NLR/PLT, NER and MNR exerted little influence on the discrimination but could enhance the calibration of the base model, and NER was proved to work best. CONCLUSIONS: Low PNR was the best indicator among neutrophils-related ratios to predict the 90-day poor outcome of AIS patients. Moreover, high NER performed best when predicting the 90-day outcome to improve the calibration of the base model.